Deaths due to delayed presentation to the hospital from fear of contracting COVID-19 during lockdown period: a tertiary care center experience. Issue 3 (4th May 2021) - Bansal, Saurabh; Roy, Moni; Chatterjee, Tulika; Roy, Ashish Kumar
ABSTRACT: Background : Sudden rise in COVID-19 cases in March 2020 due to spread of pandemic led to immediate lockdown order in many states and cities across the USA. Everyone had to stay home to stop the spread of the virus. We investigated all deaths in our hospital during lockdown period and assessed how many presented and died from non-COVID-19-related illness. Among those deaths, we assessed how many presented late due to excessive fear of catching coronavirus in the hospital and succumbed to the same illness due to very late presentation. Methods : We retrospectively reviewed charts of every patient who expired in the hospital in a 45-day period, March–April 2020. Results : Three of 107 (2.8%) deaths during lockdown period in this hospital were clearly attributable to delayed presentation arising specifically from fear of coming to the hospital. All three died from non-COVID-19-related illnesses. Conclusions : Authors hereby propose enhanced efforts in the direction to alleviate unnecessary fear among public even during lockdown. People should be encouraged to continue to access health care for serious/fatal medical conditions regardless of the pandemic.